Empirical measurement of illicit tobacco trade in the Philippines - Abola, Victor (Philippine Review of Economics, 2014)
Cigarette smuggling reduces the price of cigarettes, thwarts youth access restrictions, reduces government revenue, and undercuts the ability of taxes to reduce consumption. The tobacco industry often opposes increases to tobacco taxes on the claim that greater taxes induce more smuggling. To date, little is known about the magnitude of smuggling in the Philippines. his information is necessary to effectively address illicit trade and to measure the impacts of tax changes and the introduction of secure tax markings on illicit trade.